2011
DOI: 10.1007/s11033-011-0743-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ERCC1 and its clinicopathological correlations in non-small cell lung cancer

Abstract: Excision Repair Cross-Complementing Group 1 (ERCC1) is an important DNA repair gene, playing critical role in nucleotide excision repair pathway and having a significant influence on genomic instability. Some studies support that ERCC1 might be a potential predictive and prognostic marker in non-small cell lung cancer (NSCLC). ERCC1 has also been shown to be a promising biomarker in NSCLC treated with a cisplatin-based regimen. Therefore, the determination of ERCC1 expression at DNA, mRNA and protein level in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Previous (30,31) including our studies (28) indicated that mRNA and protein expression of ERCC1 in NSCLC tumors was higher than that in adjacent normal tissues, so it was reported that ERCC1 may be associated with the development of NSCLC. As further confirmation, in the present study, ERCC1 gene was cloned and transfected into the NSCLC H1299 cells with no intrinsic ERCC1 expression.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous (30,31) including our studies (28) indicated that mRNA and protein expression of ERCC1 in NSCLC tumors was higher than that in adjacent normal tissues, so it was reported that ERCC1 may be associated with the development of NSCLC. As further confirmation, in the present study, ERCC1 gene was cloned and transfected into the NSCLC H1299 cells with no intrinsic ERCC1 expression.…”
Section: Discussionmentioning
confidence: 64%
“…Correspondingly, the expression of the associated proteins, P-glycoprotein (P-gp) and multidrug resistanceassociated protein (MRP), had no significant difference as well between the two cell lines (C). variations with platinum-based chemotherapy response and resistance (30)(31)(32)(33). Although an exact conclusion has not been made due to the differences of these studies in trial design and laboratory tests (24,34), ERCC1 has attracted great attention of the NSCLC investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Second, low expression of ERCC1 has been shown to be associated with other genomic alterations, including those that affect sensitivity to nonplatinum chemotherapies [33,34]. Third, others have previously noted that thresholds for ERCC1 "expression" had been arbitrarily assigned and inadequately validated [35]. Fourth, several prior studies had been unable to confirm the predictive utility of ERCC1 expression in platinumtreated lung cancer patients [31,36].…”
Section: Discussionmentioning
confidence: 99%
“…For small, unifocal, superficial, low-grade bladder cancers, the estimated 5-year risk of progression to a muscle-invasive tumor is only 0.8%. Recently, several genes have been identified that are associated with bladder cancer progression and poor prognosis, such as excision repair cross-complementing group 1 (ERCC1), matrix metalloproteinase-7 (MMP-7), hyaluronidase 1 (Hyal-1) [33-35]. The latter genes point to an important role of the ECM microenvironment in bladder cancer progression.…”
Section: Discussionmentioning
confidence: 99%